The Exploration Of Early Childhood Science Through Daily Equipment: A Study At Nurul Huda Yapis Kindergarten, Keerom Regency - Pratamawati, Ayu (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2024)
This article aims to explain the use of everyday life supplies to teach science related to volume, floating, sinking and solution materials in order to improve understanding of scientific concepts, active participation, and practical skills of early childhood. This article emphasizes a qualitative approach, in data collection and analysis, by directly observing learning activities and conducting in-depth interviews with teachers of Nurul Huda Yapis Kindergarten, Keerom Regency whose data are then juxtaposed with existing literature to enrich the analysis. This article found 3 things: First, the use of daily living supplies in science practicum provides opportunities for children to experience more concrete and interactive learning. Secondly, the use of living supplies in science learning activities can increase children's engagement to develop important practical skills. Thirdly, the equipment used is easy to find and safe, so learning activities can be conducted with minimal risk. Overall, the use of everyday living supplies in science learning at Nurul Huda Yapis Kindergarten not only enriches academic understanding but also supports children's holistic development, preparing them for more in-depth learning in the future.